Posssible enhancement of long-term fear conditioning performance by cisplatin administration in rats - Goulart, Bruno Kilpp; Brunetto, Algemir Lunardi; Schwartsmann, Gilberto; Hecktheuer, Silvia Ramos; Reolon, Gustavo Kellermann; Maurmann, Natasha; Roesler, Rafael (Clinical and Biomedical Research, 2012)
Background: Neurocognitive deficits associated with chemotherapy represent an increasing concern, and the development of animal models to investigate chemotherapy-induced alterations in memory is warranted Aims: To examine the effects of systemic injection of cisplatin on formation of fear-motivated memory in rats. Methods: Male Wistar rats were given an intraperitoneal (i.p.) injection of saline or cisplatin followed by inhibitory avoidance (IA) training. Memory retention was tested 1 and 7 days after training. Control experiments using an open field were carried out to confirm the specificity of the cisplatin-induced alteration in IA performance. Results: Cisplatin induced a unexpected enhancement of IA performance measured 7 days after drug injection and training. Control experiments suggested that the effect could not be attributed to sensorimotor alterations or toxic effects. Discussion: The findings are discussed in the light of previous preclinical evidence that cancer chemotherapy can, under some conditions, lead to memory enhancement.